HUBUNGAN ANTARA GERAKAN REPETITIF DAN POSTUR KERJA DENGAN KEJADIAN CARPAL TUNNEL SYNDROME PADA PEKERJA PENGUPAS KULIT KELAPA MANUAL DI PASAR TRADISIONAL SE – KOTA SURAKARTA - Nabilah Putri Aprilia; Baju Widjasena; Suroto Suroto (Jurnal Kesehatan Masyarakat (Undip), 2021)
Traditional markets are one of the informal sectors that have an important role in people's lives. One of the commodities that being sold is coconut. Manual coconut shell peeler workers when working often perform repetitive movements and poses in awkward work postures, especially extreme wrist positions for long periods of time. Its a risk for the occurrence of Carpal Tunnel Syndrome in workers. This research aim to find out the corellation between repetitive movements and work postures with the incidence of CTS in Manual Coconut Shell Peeler Workers in Traditional Markets of Surakarta City. This research was quantitative with cross sectional method. Research’s population was manual coconut shell peeler workers in traditional markets throughout the city of Surakarta. Samples was taken by incidental technique consisting of 30 respondents from 5 traditional markets in Surakarta. The independent variables are repetitive movements and work postures. The dependent variable is the incidence of CTS, while the confounding variables are history of diseases or acute trauma, pregnancy, and nutritional status. Data were collected using google form and analyzed using Chi - Square and Spearman Rank. The results showed that the p-value of the repetitive movement with the incidence of CTS was 0.003<0.05 performed by Chi-Square test, while the p-value of work posture with the incidence of CTS was 0.013<0.05 performed by Spearman Rank. There is a corellation between repetitive movements and work postures with the incidence of CTS in manual coconut shell peelers in traditional markets throughout Surakarta City.